2018
DOI: 10.18805/ijar.b-3578
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic marker for prolactin gene related to milk yield in pedigreed Sahiwal population

Abstract: The study was conducted to identify the genetic marker for prolactin gene related to milk yield in pedigreed Sahiwal population. PCR-RFLP was carried out by using Rsa1 restriction endonuclease and revealed three genotypes GG, GA and AA in Sahiwal population. The frequency of G and A allele of Prolactin gene (exon 3) was estimated as 0.575 and 0.425, whereas the frequencies of GG, GA and AA genotypes for Prolactin gene (exon 3) were estimated as 0.45, 0.25 and 0.30, respectively. Regression analysis inferred th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Kumari et al (2008) in India reported frequencies of AA, BB and AB genotypes to be 0.22, 0.13 and 0.65 in Jersey cattle with allelic frequencies of 0.55 for A allele and 0.45 for B allele. Karuthadurai et al (2019) reported also in India that the frequencies of AA, GG and GA genotypes of Sahiwal cattle were 0.30, 0.45 and 0.25, respectively with allelic frequencies of 0.425 for A allele and 0.575 for G allele. In Croatia, Mauriae et al (2017) stated that most of the animals of Simmental and crossbred Holstein cattle were genotyped as GG homozygous genotype for PRL gene.…”
Section: Genotypic and Allelic Frequencies In Each Herdmentioning
confidence: 87%
See 2 more Smart Citations
“…Kumari et al (2008) in India reported frequencies of AA, BB and AB genotypes to be 0.22, 0.13 and 0.65 in Jersey cattle with allelic frequencies of 0.55 for A allele and 0.45 for B allele. Karuthadurai et al (2019) reported also in India that the frequencies of AA, GG and GA genotypes of Sahiwal cattle were 0.30, 0.45 and 0.25, respectively with allelic frequencies of 0.425 for A allele and 0.575 for G allele. In Croatia, Mauriae et al (2017) stated that most of the animals of Simmental and crossbred Holstein cattle were genotyped as GG homozygous genotype for PRL gene.…”
Section: Genotypic and Allelic Frequencies In Each Herdmentioning
confidence: 87%
“…However, the polymorphism in exon 3 and 4 of the prolactin gene in dairy cattle was clarified and protocoled by several investigators (e.g. Zhang et al, 2008;Hu et al, 2009;Mehmannavaz et al, 2009;Das et al, 2012;Karuthadurai et al, 2019;Bayıl and Bozkurt, 2019;Dudule et al, 2020;Shah et al, 2021, andSamuel et al, 2023).…”
Section: Animals Used and Genomic Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation